The Stratification Concept of Clear Meaning Nash Text and Its Application in The Field of Family Law - Muhammad Faruq Bahril; Zainal Azwar; Muhamad Ferdian (The Indonesian Journal of Islamic Law and Civil Law, 2024)
The texts of Qur’an and Sunnah are sometimes formulated in clear form (wadih al-ma’na) and the other times formulated in unclear form (khafiy al-ma’na). The clear forms (wadih al-ma’na) are various levels and should be explained so that prevents a fundamental mistake in the law formulation. The clear forms (wadih al-ma’na) induce argue between Islamic lawyers that determines the law construction. This article is to explain the concept of clear texts stratification and analyze its implementation in the law construction between scholars. This article is normative law research with ushul fiqh approach. The data analyzed are gathered from secondary sources such as classic ushul fiqh books of Hanafiy and Shafii schools as the main source. The other law source such as books and articles OJS-based are involved as well. The data obtained are analyzed within descriptive analysis with reduction, display and verification technique. This research results that different views in the text stratification between scholars is merely redactional (lafziy) not substantive (ma’nawiy). The stratification between scholars does not result a substantive difference in products of law, especially law of marriage and inheritance. Different formulation in the text stratification of sharia enrich literature discussion and knowledge of ushul fiqih for the experts of law in formulating law.